Pandangan Islam tentang Korupsi - Umam, Muchammad Helmi (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2013)
This research aims to find an adequate philosophical explanation of the responsibilities of Muslim society in Indonesia with the handling of corruption. Islam is the largest religion in Indonesia that should be responsible for the removal of culture of corruption. This research focuses on the discussion of Islamic values of anti-corruption, the principle of balance in view of corruption as well as the principle of punishment. The analysis to use is to understand the phenomenon of law enforcement through the textual frame in Islamic context. The conclusions are to look back on overcoming spirit of anti-corruption, corruption should saw proportionally, the mechanism of punishment and its relation to the education of humanity.